State aid in the European Union in the period of the economic crisis - Joanna Działo (Comparative Economic Research. Central and Eastern Europe, 2014)
The global economic crisis has brought about the need for States' involvement to rescue many business entities from bankruptcy, initially in the financial sector, and at a later stage of the crisis in the real economy. In the countries of the European Union, these measures take the form of state aid, which is specifically regulated as it bestows benefits on its beneficiaries and therefore violates the rules of market competition. Thus, the provision of state aid is controversial, since it potentially adversely affects the competition policy pursued in the EU. This paper aims to analyse and evaluate the volume of state aid granted in the EU countries during the economic crisis and its potential impact on the health of the economy and the public finance sector.
Keywords: 330; state aid; economic crisis; crisis and non-crisis aid; financial sector; real economy